Euclid preparation: LXIV. The cosmic dawn survey (DAWN) of the Euclid deep and auxiliary fields - McPartland, Conor; Jahnke, Knud; Sakr, Ziad; Schirmer, Mischa; Seidel, Gregor; Maturi, Matteo (Astronomy and astrophysics, 2025)
Euclid will provide deep near-infrared (NIR) imaging to ∼26.5 AB magnitude over ∼59 deg2 in its deep and auxiliary fields. The Cosmic DAWN survey combines dedicated and archival UV–NIR observations to provide matched depth multiwavelength imaging of the Euclid deep and auxiliary fields. The DAWN survey will provide consistently measured Euclid NIR-selected photometric catalogues, accurate photometric redshifts, and measurements of galaxy properties to a redshift of z ∼ 10. The DAWN catalogues include Spitzer IRAC data that are critical for stellar mass measurements at z ≳ 2.5 and high-z science. These catalogues complement the standard Euclid catalogues, which will not include Spitzer IRAC data. In this paper, we present an overview of the survey, including the footprints of the survey fields, the existing and planned observations, and the primary science goals for the combined data set.
Euclid Collaboration: C.J.R. McPartland, K. Jahnke, Z. Sakr, M. Schirmer, G. Seidel, M. Maturi und 284 weitere
Online veröffentlicht: 28. März 2025
Gesehen am 26.01.2026